Transcriptional Landscape of Waddlia chondrophila Aberrant Bodies Induced by Iron Starvation - Ardissone, Silvia (Microorganisms, 2020)
Chronic infections caused by obligate intracellular bacteria belonging to the Chlamydiales order are related to the formation of persistent developmental forms called aberrant bodies (ABs), which undergo DNA replication without cell division. These enlarged bacteria develop and persist upon exposure to different stressful conditions such as β-lactam antibiotics, iron deprivation and interferon-γ. However, the mechanisms behind ABs biogenesis remain uncharted. Using an RNA-sequencing approach, we compared the transcriptional profile of ABs induced by iron starvation to untreated bacteria in the Chlamydia-related species Waddlia chondrophila, a potential agent of abortion in ruminants and miscarriage in humans. Consistent with the growth arrest observed following iron depletion, our results indicate a significant reduction in the expression of genes related to energy production, carbohydrate and amino acid metabolism and cell wall/envelope biogenesis, compared to untreated, actively replicating bacteria. Conversely, three putative toxin-antitoxin modules were among the most up-regulated genes upon iron starvation, suggesting that their activation might be involved in growth arrest in adverse conditions, an uncommon feature in obligate intracellular bacteria. Our work represents the first complete transcriptomic profile of a Chlamydia-related species in stressful conditions and sets the grounds for further investigations on the mechanisms underlying chlamydial persistence.